Towards Mongolia’s Long-Term Development Policy Vision 2050 : Advancing Education Equity, Efficiency and Outcomes - Mongolia Ministry of Education, Culture, Science and Sports (World Bank, Ulaanbaatar, 2020)
This report seeks to synthesize and analyze education outcomes with a view of identifying the main priorities for strengthening the education sector in support of Mongolia’s Sustainable Development Vision 2050. The report highlights data and findings generated from a series of source reports (see bibliography) related to the goals and targets set out in the Vision 2050. The report is composed of six thematic chapters: Access; Equity; Internal Efficiency, Education Cost and Finance; External Efficiency; Management. Each chapter will include an overview of the current situation and recent development with a focus on, key achievements and persistent challenges. As a synthesis report, the information on each topic is not exhaustive but rather seeks to present key findings. Specific activities highlighted in the Vision 2050 have been included at the beginning of each chapter and a complete mapping by activity is annexed (Annex 1. Vision 2050 Chapter mapping). This synthesis report draws on conclusions, finding, data and surveys produced in collaboration with MECSS by the Asian Development Bank, the Global Partnership for Education and the World Bank. The synthesis also draws from key UNESCO reports. The scope, research, and focus of the source reports differ, and precise findings are, on occasions, incongruent however the overall conclusions are fundamentally compatible. Whereas most of the source reports focus on one or two key stages, the synthesis report seeks to extract cross-cutting and/or recurring challenges that have an impact, positive or negative, on equity, efficiency and outcomes which ultimately may contribute to the implementation of Vision 2050. Mongolia’s State Education Policy (2014-2024) states: ‘Education is the main key factor of each citizen’s lifelong support and guarantee of life quality, and of the State’s societal and economical, science and technological development, and guarantee of national independence and security. Mongolian State shall develop education as a leading sector in society’.